2014
DOI: 10.1111/gcb.12757
|View full text |Cite
|
Sign up to set email alerts
|

Polygonal tundra geomorphological change in response to warming alters future CO2 and CH4 flux on the Barrow Peninsula

Abstract: The landscape of the Barrow Peninsula in northern Alaska is thought to have formed over centuries to millennia, and is now dominated by ice-wedge polygonal tundra that spans drained thaw-lake basins and interstitial tundra. In nearby tundra regions, studies have identified a rapid increase in thermokarst formation (i.e., pits) over recent decades in response to climate warming, facilitating changes in polygonal tundra geomorphology. We assessed the future impact of 100 years of tundra geomorphic change on peak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
169
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 106 publications
(175 citation statements)
references
References 93 publications
(192 reference statements)
6
169
0
Order By: Relevance
“…Ground surveys of waterbody surface area were available for only a few study sites. Accuracy ranged between 89 % for object-oriented mapping of multispectral imagery (Lara et al, 2015), 93 % for object-oriented mapping of panchromatic imagery (Andresen and Lougheed, 2015), and more than 95 % for a supervised maximum-likelihood classification of multispectral aerial images (Muster et al, 2012). Errors in the classification may be largely due to commission errors: i.e., the spectral signal is misinterpreted as water where in reality it may be land surface.…”
Section: Classification Accuracy and Variabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Ground surveys of waterbody surface area were available for only a few study sites. Accuracy ranged between 89 % for object-oriented mapping of multispectral imagery (Lara et al, 2015), 93 % for object-oriented mapping of panchromatic imagery (Andresen and Lougheed, 2015), and more than 95 % for a supervised maximum-likelihood classification of multispectral aerial images (Muster et al, 2012). Errors in the classification may be largely due to commission errors: i.e., the spectral signal is misinterpreted as water where in reality it may be land surface.…”
Section: Classification Accuracy and Variabilitymentioning
confidence: 99%
“…Due to their small surface areas and shallow depths, ponds are especially prone to change; various studies reported ponds drying out or increasing in abundance due to new thermokarst or the drainage of large lakes (Jones et al, 2011;Andresen and Lougheed, 2015;Liljedahl et al, 2016). Such changes in surface inundation may significantly alter regional water, energy, and carbon fluxes (Watts et al, 2014;Lara et al, 2015). Both the monitoring and modeling of pond and lake development are therefore crucial to better understand the trajectories of Arctic land cover dynamics in relation to climate and environmental change.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of Carex aquatilis, Eriophorum scheuchzeri and Dupontia fisheri characterizes well the typical vegeta- tion of Arctic wetlands (Jorgenson et al, 2013;Sandvik and Odland, 2014;Lara et al, 2015) whilst that of Arctagrostis latifolia, Luzula and Salix spp. are common features of Arctic mesic environments (Audet et al, 2007;Sjögersten et al, 2008).…”
Section: Vegetation Changesmentioning
confidence: 83%
“…There is evidence for a strong vegetation control on methane emission from wetlands (Olefeldt et al, 2013;Lara et al, 2015;McEwing et al, 2015;Tveit et al, 2015). In wet polygonal tundra of Northern Siberia, Kutzbach et al (2004) found for instance that dense Carex aquatilis stands emitted more methane than sites with low Carex densities.…”
Section: Impacts On Ecosystemsmentioning
confidence: 99%
“…The large uncertainty associated with this estimation is due to the spatial and temporal 15 complexity of the Arctic ecosystem. The unique polygonal ground in Arctic coastal plain tundra creates natural gradients in hydrology, snow pack depth and density, and soil organic carbon storage that control CH 4 fluxes Lara et al, 2015). Thermal contraction processes create cracks in the tundra soil, which can fill with water that freezes to produce massive ground ice (French, 2007).…”
Section: Introductionmentioning
confidence: 99%